Effectiveness of Glycyrrhizinic Acid (Glizigen) and an Immunostimulant (Viusid) to Treat Anogenital Warts. (29th July 2012) - Domínguez Gómez, José; Simón, Ramón Daniel; Abreu Daniel, Alfredo; Zelenkova, Hana
Abstract : Genital warts are benign proliferations of skin and mucosa caused by the human papillomavirus infection (hereinafter referred to as HPV). It is one of the most common sexually transmitted diseases in the world, whose incidence rate has increased in the last three decades. Current treatment involves the physical destruction of the infected cells. The fact that there are many different types of treatment goes to show that none of them are uniformly effective or directly antiviral. Objective . Demonstrate the efficacy of Glizigen in the III-phase clinical trial combined with a food supplement (VIUSID) formulated to boost the immune system when treating external anogenital warts. Design . 100 patients clinically diagnosed with anogenital lesions were included in the trial and assigned to two groups of 50 individuals. Those from one group where treated with Glizigen and Viusid and those from the other group with 25% podophyllin in alcohol, the results from each were then compared. Results . The combined Glizigen-Viusid treatment was seen to have an 87.5% efficacy rate, which was slightly more than that of the treatment with podophyllin, and there were hardly any adverse reactions reported during the treatment. Conclusions . the combined Glizigen-Viusid treatment was effective in treating genital warts.